Cerebrospinal Fluid Extracellular Vesicles Undergo Age Dependent Declines and Contain Known and Novel Non-coding RNAs - Tietje, Ashlee; Maron, Kourtney N.; Wei, Yanzhang; Feliciano, David M. (PloS one, 2014)
Brain development requires precise orchestration of cellular events through the coordinate exchange of information between distally located cells. One mechanism by which intercellular communication is achieved is through the transfer of extracellular vesicles (EVs). Exosomes are EVs that carry lipids, nucleic acids, and proteins and are detectable in most biological fluids including cerebrospinal fluid (CSF). Here we report that CSF EV concentrations undergo age dependent fluctuations. We characterized EV RNA content by next generation small RNA sequencing and miRNA microarray analysis and identified a temporal shift in CSF EV content. CSF EVs encapsulated miRNAs that contain a conserved hnRNPA2/B1 recognition sequence. We found that hnRNPA2/B1-containing EVs were produced by choroid plexus epithelial cells and that hnRNPA2/B1 containing EVs decreased with age. These results provide insight into EV exchange of miRNAs within the central nervous system and a framework to understand how changes in EVs may have an important impact on brain development.